Shear Strength Models for Reinforced Concrete Slender Beams: A Comparative Study. (November 2018) - Ahmad, Subhan; Bhargava, Pradeep
Abstract: Shear strength is one of the most widely investigated parameter in reinforced concrete (RC) beams. Numerous papers are published in last 66 years which investigate experimentally and theoretically the shear strength of RC beams without shear reinforcement. In this paper a database on shear strength of 719 RC beams without transverse reinforcement is generated from experimental results published between 1952 and 2018. Well-known shear strength models proposed in the literature are summarized and evaluated through comparison with the experimental results of generated database. It was found that models proposed by Niwa et al. (1986) and Zararis and Papadakis (2001) predicts shear strength of RC beams more accurately than the other models. The former model gives an average strength ratio of 1.05 with a coefficient of variation of 29% while the latter yielded an average strength ratio of 1.10 with a coefficient of variation of 29%. A detailed evaluation in various ranges of parameters revealed that both the models gives unconservative results of shear strength for beams with concrete compressive strength >90 MPa. Parametric study of the two models within the individual test series showed that model of Niwa et al. does not capture the size effect in RC beams very effectively while the model of Zararis and Papadakis yields uniform results over the whole range of experimental data. Highlights: A database on shear strength of 719 RC beams without transverse reinforcement is generated from experimental results. Shear strength models are summarized and evaluated through comparison with the experimental results of database Models proposed by Niwa et al. and Zararis and Papadakis predicts shear strength of RC beams more accurately than the other models Models of Niwa et al. and Zararis and Papadakis gives unconservative results of shear strength for beams with concrete compressive strength > 90 MPa. Parametric study of the two models showed that model of Niwa et al. does not capture the size effect in RC beams as effectively as the model of Zararis and Papadakis.